Pengaruh Pembuatan Ecobrick Terhadap Sikap Peduli Lingkungan Pada Pembelajaran IPAS Di Kelas V Sekolah Dasar - Sinaga, Ruth Silvia; Anggraini, Dwi (Universitas Bengkulu, 2025)
Ecobricks utilize compressed plastic waste contained within plastic bottles to produce valuable goods through recycling and repurposing. This study aims to determine the effects of ecobricking on attitudes towards environmental care in scientific instruction among fifth-grade students in Elementary School cluster XIXI in Bengkulu City. This study examines the differences in values before and after ecobricking using a one-group pre-test-post-test approach. The methodology utilized is a quantitative approach, specifically employing the Pre-Experimental Design process. This study encompasses all children in grade V from cluster XIX of Elementary Schools in Bengkulu City. The selection process considered several factors and ultimately included only one school, SDN 69 Bengkulu City. The VB class of SDN 69 Elementary School in Bengkulu City was selected as the sample for the study. Applying purposive sampling for the purpose of sampling. The study utilized a closed questionnaire with a Likert scale, which was administered both before and after the experiment. The acquired data are analyzed using quantitative analysis. The significance of the disparity between the periods before and after the therapy was evidenced by the findings of the post-test analysis. Subsequently, a t-test, which is a hypothesis test, is conducted utilizing a t value of 7.780, surpassing the critical value of 2.005 from the t table. The results of the t-test reveal that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This suggests that the loading of ecobricks has a significant impact on students' attitudes towards environmental care.